2010
DOI: 10.1163/156855109x434838
|View full text |Cite
|
Sign up to set email alerts
|

Tensile Properties of Carbon Fiber Composites with Different Resin Compositions at Cryogenic Temperatures

Abstract: In this study, the tensile properties of carbon fiber reinforced polymer (CFRP) composites with different resin compositions were investigated in order to develop advanced composite materials for cryogenic use. Thermo-mechanical cyclic loading (up to 6 cycles) was applied to CFRP unidirectional laminate specimens from room temperature to −150 • C. Tensile tests were then performed at −150 • C using an environmental test chamber. In addition, matrix-dominant properties such as the transverse and in-plane shear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 11 publications
1
21
0
Order By: Relevance
“…The result showed that, the tensile strength decreased significantly with increasing temperature and remained almost stable after the polymer exceeds its glass transition temperature. On the other side, at cryogenic temperatures, it was shown that CFRP composites had better tensile properties [9]. The tensile properties of FRP composites have also been affected by curing temperature used during fabrication of composite materials.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The result showed that, the tensile strength decreased significantly with increasing temperature and remained almost stable after the polymer exceeds its glass transition temperature. On the other side, at cryogenic temperatures, it was shown that CFRP composites had better tensile properties [9]. The tensile properties of FRP composites have also been affected by curing temperature used during fabrication of composite materials.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They can be produced in uniform thickness with high temperature and vacuum pressure while the additional autoclave pressure helps improve the quality of surface profile. And its high bonding strength between layers improves fiber volumetric rate and eases elimination of bubbles between materials [6].…”
Section: Molding Process Of Carbon Fiber Pre-pregmentioning
confidence: 99%
“…DICY (aliphatic polyamine dicyandiamide) and DCMU (diuron) were incorporated as a hardener and an accelerator, respectively. In addition, CTBN-(carboxyl terminated butadiene acrylonitrile) modified rubber was added to the resin mixture as an additive to improve the fracture toughness at cryogenic temperatures [11].…”
Section: Composite/aluminum Ring Specimensmentioning
confidence: 99%
“…To this end, composite/aluminum ring specimens were manufactured using carbon fiber and Type B epoxy resin which had been developed for cryogenic use [11]. In the experiments, thermal strains of the ring specimens were measured during cooling from RT to À150°C.…”
Section: Introductionmentioning
confidence: 99%